Innovation Shortfalls - William Maloney; Andrés Rodríguez-Clare (Inter-American Development Bank, Research Department, 2005)
There is a common perception that low productivity or low growth is due to what can be called an `innovation shortfall,` usually identified as a low rate of investment in research and development (RD) compared with some high-innovation countries. The usual reaction to this perceived problem is to call for increases in RD investment rates, usually specifying a target that can be as high as 3 percent of GDP. The problem with this analysis is that it fails to see that a low RD investment rate may be appropriate given the economy`s pattern of specialization, or may be just one manifestation of more general problems that impede accumulation of all kinds of capital. When does a country suffer from an innovation shortfall above and beyond the ones that should be expected given its specialization and accumulation patterns? This is the question tackled in this paper. First, it shows a simple way to estimate the RD gap that can be explained by a country`s specialization pattern, and illustrates this with the case of Chile. The analysis finds that although Chile`s specialization in natural-resource-intensive sectors explains part of its RD gap, a significant shortfall remains. Second, it shows how a calibrated model can be used to determine the RD gap that should be expected given a country`s investment in physical and human capital. If the actual RD gap is above this expected gap, the country suffers from a true innovation shortfall.
Keywords: 330; Innovation; Produktivität; Investition; Internationale Arbeitsteilung; Theorie; Chile